Nanoscale characterization of the temporary adhesive of the sea urchin Paracentrotus lividus - Viana, Ana S.; Santos, Romana (Beilstein Journal of Nanotechnology, 2018)
Background: Unlike the thin homogeneous films that are typical for adhesives produced by humans, biological adhesives present complex hierarchical micro- and nanostructures. Most studies on marine adhesives have focused on permanent adhesives, whereas the nanostructures of nonpermanent, temporary or reversible adhesives have only been examined in some organisms such as marine flatworms, barnacle cyprids, freshwater cnidaria and echinoderms such as sea cucumbers and sea stars. In this study, the first nanoscale characterization of sea urchin temporary adhesives was performed using atomic force microscopy (AFM).Results: The adhesive topography was similar under dry and native (seawater) conditions, which was comprised of a honeycomb-like meshwork of aggregated globular nanostructures. In terms of adhesion forces, higher values were obtained in dry conditions, reaching up to 50 nN. Under native conditions, lower adhesive forces were obtained (up to 500 pN) but the adhesive seemed to behave like a functional amyloid, as evidenced by the recorded characteristic sawtooth force–extension curves and positive thioflavin-T labelling.Conclusion: Our results confirm that like other temporary adhesives, the sea urchin adhesive footprint nanostructure consists of a meshwork of entangled globular nanostructures. Under native conditions, the adhesive footprints of the sea urchin behaved like a functional amyloid, suggesting that among its proteinaceous constituents there are most likely proteins with amyloid quaternary structures or rich in β-sheets. These results extend our knowledge on sea urchin adhesive composition and mechanical properties essential for the engineering of biomimetic adhesives.
Keywords: adhesive footprint; atomic force microscopy; nanomechanical properties; sea urchin; temporary adhesion

(untitled) - S. Mostaert, A.; Crockett, R.; Kearn, G.; Cherny, I.; Gazit, E.; C. Serpell, L.; P. Jarvis, S. (Arch. Histol. Cytol., 2009)

(untitled) - Phang, I. Y.; Aldred, N.; Clare, A. S.; Vancso, G. J. (J. R. Soc., Interface, 2008)

(untitled) - Phang, I. Y.; Aldred, N.; Ling, X. Y.; Tomczak, N.; Huskens, J.; Clare, A. S.; Vancso, G. J. (J. Adhes., 2009)

(untitled) - Phang, I. Y.; Aldred, N.; Ling, X. Y.; Huskens, J.; Clare, A. S.; Vancso, G. J. (J. R. Soc., Interface, 2010)

(untitled) - Rodrigues, M.; Leclère, P.; Flammang, P.; Hess, M. W.; Salvenmoser, W.; Hobmayer, B.; Ladurner, P. (BMC Zool., 2016)

(untitled) - Demeuldre, M.; Chinh Ngo, T.; Hennebert, E.; Wattiez, R.; Leclère, P.; Flammang, P. (Biointerphases, 2014)

(untitled) - Hennebert, E.; Viville, P.; Lazzaroni, R.; Flammang, P. (J. Struct. Biol., 2008)

Biological and Biomimetic Adhesives - Higgins, L.; Mostaert, A. (Qualitative and Quantitative Study of Spiny Starfish (Marthasterias Glacialis) Footprints Using Atomic Force Microscopy)

(untitled) - Niu, Y.; Matos, A. I.; Abrantes, L. M.; Viana, A. S.; Jin, G. (Langmuir, 2012)

(untitled) - Marquês, J. T.; de Almeida, R. F. M.; Viana, A. S. (Soft Matter, 2012)

(untitled) - Kearn, G. C.; Evans-Gowing, R. (Int. J. Parasitol., 1998)

(untitled) - Hamwood, T. E.; Cribb, B. W.; Halliday, J. A.; Kearn, G. C.; Whittington, I. D. (Folia Parasitol., 2002)

Echinoderm Studies - Flammang, P. (Adhesion in echinoderms, 1996)

(untitled) - Hennebert, E.; Santos, R.; Flammang, P. (Zoosymposia, 2012)

(untitled) - Flammang, P.; Demeulenaere, S.; Jangoux, M. (Biol. Bull. (Chicago, IL, U. S.), 1994)

(untitled) - Flammang, P.; Michel, A.; Van Cauwenberge, A.; Alexandre, H.; Jangoux, M. (J. Exp. Biol., 1998)

(untitled) - Santos, R.; Flammang, P. (Biofouling, 2006)

(untitled) - Santos, R.; da Costa, G.; Franco, C.; Gomes-Alves, P.; Flammang, P.; Coelho, A. V. (Mar. Biotechnol., 2009)

Echinodermata - Flammang, P.; Santos, R.; Haesaerts, D. (Echinoderm Adhesive Secretions: From Experimental Characterization to Biotechnological Applications)

(untitled) - Wiegemann, M.; Watermann, B. (J. Adhes. Sci. Technol., 2003)

(untitled) - Waite, J. H.; Andersen, N. H.; Jewhurst, S.; Sun, C. (J. Adhes., 2005)

(untitled) - Zhang, M.; Liu, M.; Bewick, S.; Suo, Z. (J. Biomed. Nanotechnol., 2009)

Functional Surfaces in Biology - Santos, R.; Hennebert, E.; Coelho, A. V.; Flammang, P. (The Echinoderm Tube Foot and its Role in Temporary Underwater Adhesion, 2009)

(untitled) - Zitzler, L.; Herminghaus, S.; Mugele, F. (Phys. Rev. B, 2002)

(untitled) - Gade Malmos, K.; Blancas-Mejia, L. M.; Weber, B.; Buchner, J.; Ramirez-Alvarado, M.; Naiki, H.; Otzen, D. (Amyloid, 2017)

(untitled) - Mostaert, A. S.; Higgins, M. J.; Fukuma, T.; Rindi, F.; Jarvis, S. P. (J. Biol. Phys., 2006)